Coexistent gastric MALT lymphoma and Kaposi sarcoma in an HIV positive patient. Issue 4 (1st April 1999) - Chetty, R; Pillay, S V
Abstract : A 47 year old HIV positive male presented with haematemesis and epigastric pain. A gastrectomy was performed for intractable bleeding. The cause of the haematemesis proved to be a Kaposi sarcoma of the stomach which had resulted in mucosal ulceration. Several other smaller foci of Kaposi sarcoma were also present. Coexistent with the Kaposi sarcoma was a dense lymphoid infiltrate with lymphoid follicles and reactive germinal centres. Centrocyte-like cells caused marked effacement and destruction of gastric glands with the formation of lymphoepithelial lesions, typical of a MALT lymphoma. These cells were of B cell lineage and some expressed the HIV antigen, p24. Follicular dendritic cells and macrophages within germinal centres were also p24 positive. Immunohistochemistry and in situ hybridisation did not detect Epstein-Barr virus. Although Helicobacter pylori was not identified by light microscopy in the sections sampled, this does not preclude its possible role, with other cofactors such as HIV, in the causation of the MALT lymphoma.